Sistem Informasi Akuntansi dan Internal Control terhadap Efektivitas Kinerja Karyawan Dimoderasi oleh Penerapan Software Akuntansi - Sihar Tambun; Ayu Pratiwi (AFRE (Accounting and Financial Review), 2022)
The purpose of this study was to examine the accounting information system, internal control and accounting software on the effectiveness of employee performance. and to examine the effect of moderating accounting information systems and internal control on the effectiveness of employee performance. The research method used is quantitative with the collection technique using a questionnaire. The number of samples used is 299 respondents. The sample was tested for validity and reliability testing. From the results of hypothesis testing, it proves that there is an influence of the accounting information system on employee performance, the influence of internal control on employee perfor-mance, the influence of the application of accounting software on employee performance, and the influence of accounting software moderation on the influence of internal control on employee performance. However, there is no effect of accounting software moderation on the effect of accounting information systems on employee performance.DOI: https://doi.org/10.26905/afr.v5i2.7831